Outdoor tourism demand segmentation: a case study from North of Portugal - Scalabrini, E.C.B. (2022)
This research aimed to segment the market of visitors who practise outdoor activities in the North region of Portugal based on their motivations. To this end, a survey was applied to visitors who practised outdoor activities in the region. The data was collected between June and September of 2021, and a final sample of 200 valid questionnaires was obtained. ln an overall analysis of the socio-demographic and professional profile of the respondents, it can be said that the sample is constituted by women (50.5%), aged between 28-38 or over (58.5%), with higher education levels (70.5%), single (53.3%) and Portuguese (94.5%), with an average monthly income between 601€ and 2400€ (74%). Most of them live in the Porto Metropolitan Area (25%) located in the Northern region of Portugal. Relating to outdoor activities, 35.5% of the sample occasionally practise these activities in their residence area, and 20% practise 1-2 times a week. The activities most practised were walking/hiding (28.8%), running (11.7%), and cycling (9.5%). This research demonstrates that segmentation of outdoor tourism demand in North of Portugal should set out marketing and promotion strategies in different destinations, attracting demand, from outside the region and according to their preferences. Therefore, this study contributes to the literature by expanding the discussion on outdoor tourism segmentation, an underestimated topic.